If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(v + 2) = 7(v + 1) Reorder the terms: 5(2 + v) = 7(v + 1) (2 * 5 + v * 5) = 7(v + 1) (10 + 5v) = 7(v + 1) Reorder the terms: 10 + 5v = 7(1 + v) 10 + 5v = (1 * 7 + v * 7) 10 + 5v = (7 + 7v) Solving 10 + 5v = 7 + 7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-7v' to each side of the equation. 10 + 5v + -7v = 7 + 7v + -7v Combine like terms: 5v + -7v = -2v 10 + -2v = 7 + 7v + -7v Combine like terms: 7v + -7v = 0 10 + -2v = 7 + 0 10 + -2v = 7 Add '-10' to each side of the equation. 10 + -10 + -2v = 7 + -10 Combine like terms: 10 + -10 = 0 0 + -2v = 7 + -10 -2v = 7 + -10 Combine like terms: 7 + -10 = -3 -2v = -3 Divide each side by '-2'. v = 1.5 Simplifying v = 1.5
| 5x-2=5+3x | | -3(z+3)=2(4-z) | | 9x-(2x+5)=5x+(3x-8) | | 6+5e=2e-9 | | 3c+1=5c-15 | | 4(2-s)=-6s-2 | | 2w=3 | | 27=x*9 | | 84=w^2+5w | | 7M=3M+12 | | 2.8*6.7= | | 6=-2x-4 | | 1+3x=16-2 | | 2+5x+3x=8+3x | | x-4y=7 | | x-5=x | | 4x+1=5+3x | | 8x+2=6x+4 | | 3x+5=12+2x | | 15=x-1 | | 18=x+15 | | 5x+2=8x+3x | | 27=15m | | 7a=18 | | 1141=9x+4y | | Y=27 | | 2t=-2 | | X^2+y^2-10=50 | | 2c-2=4c-6 | | 14x=26 | | 9+4t=7t+15 | | x-2=x-4 |